Albert Camus and Prometheus - Voisset-Veysseyre, Cécile (Amaltea. Journal of Myth Criticism, 2012)
The myth of Prometheus talks about rebellion as a beginning. The Titan who stood up to Zeus and stole fire in order to bring it to men became a model of humanity, a figure of a saving rebelliousness and a symbol of hope in human race. It is the story of a gesture in the very middle of wilderness where the hero is tied to a rock from which he is supposed to be untied. Albert Camus’s Prometheus belongs to a laicized story of creation. “What is an artist?” asks the writer, who universalizes a Greek and Oriental myth; the modeling, the titanic mark of the creature, challenges our understanding of reality through art.